‘Just because we can, does it mean we should?’ The integrated data infrastructure in Aotearoa, and its implications for Māori - Boey, Daphne; Campbell-Meier, Jennifer; Lilley, Spencer; Toland, Janet (Information Research an international electronic journal, 2025)
Introduction. This paper discusses the importance of data in Māori society and Māori Data Sovereignty in Aotearoa New Zealand. Method. A descriptive case study is presented of the Integrated Data Infrastructure (IDI), a trove of interlinked and de-identified data about people that is the cornerstone for evidence-based policy decisions in Aotearoa New Zealand. The case study highlights existing issues Māori have with regards to the collection and use of their data. Analysis. The IDI is examined in relation to its historical and cultural context, taking into account the ongoing impacts of colonisation with respect to the ownership and management of data. Discussed are the safety mechanisms of the IDI, secondary data use, and social & cultural licence. Conclusions. The paper concludes by acknowledging that the right of Māori to exercise their self-determination of how data is collected, stored, and accessed remains aspirational and there is a need for Māori to have greater control over the data and who has access to it.